The Influence of Leadership Style and Work Loyalty on Employee Performance with Organizational Culture as a Moderating Variable at PT Smart Retail Perkasa - Andry Sutio; Pras Rendi; Nunung Ayu Sofianti; Rama Chandra Jaya (GoAcademica Research & Publishing, 2026)
Employee performance tends to improve alongside higher-quality leadership and stronger work loyalty. Positive and significant regression coefficients indicate that both variables are key determinants of performance. A strong organizational culture further reinforces these relationships, highlighting the alignment between leadership practices, employee attitudes, and organizational values in enhancing work outcomes, while also offering practical guidance for retail management. This study aims to examine the influence of leadership style and work loyalty on employee performance, with organizational culture serving as a moderating variable at PT Smart Retail Perkasa. The research employs a causal quantitative approach. Data were collected through questionnaire distribution to employees and analyzed using multiple linear regression and moderation analysis with bootstrapping techniques to statistically verify the relationships among variables. The findings reveal that leadership style has a positive and significant effect on employee performance (t = 2.628; p = 0.009). Similarly, work loyalty demonstrates a positive and significant influence on performance (t = 2.586; p = 0.010). Organizational culture not only directly affects employee performance but also strengthens the effect of leadership style on performance (t = 3.401; p = 0.001) and amplifies the influence of work loyalty on performance (t = 2.760; p = 0.006). These results indicate that employee performance increases when effective leadership and high work loyalty are supported by a strong organizational culture. This study confirms that employee performance is shaped by leadership style and work loyalty, with organizational culture acting as a reinforcing factor. Therefore, improving performance requires the integration of effective leadership, strong employee loyalty, and a cohesive organizational culture.